Massive right atrial myxoma with dyspnea at rest in an elderly patient: A case report - Romanović, Radoslav; Ratković, Nenad; Davičević, Žaklina; Ilić, Radoje (Vojnosanitetski pregled, 2015)
Introduction. Primary heart tumors are extremely rare and myxoma is the most common type of these tumors. Although intra-atrial presentation is a predilection place, right atrial localization is atypical. The symptom triad is characteristic in the clinical presentation of the tumor: embolic complication, intracardiac blood flow obstruction and systemic manifestations like elevated erythrocyte sedimentation rate, fever, anemia, body weight loss. Case report. We presented an elderly female patient with massive myxoma in the right atrium, 77 × 44 mm in diameter, which filled the entire right atrium and spread into the right ventricle, causing the tricuspid valve obstruction and dyspnea. It was visualized by transthoracic echocardiography and small and insignificant pericardial effusion was also seen. After surgical removal of the tumor, the patient remained without any symptoms and pericardial effusion. Conclusion. Tumors of the right heart have to be considered in the differential diagnosis of unexplained dyspnea in elderly patients. Transthoracic echocardiography is certainly necessary and mostly available diagnostic tool that can be of great help in diagnosing heart tumor as well as planning cardiac surgery, as it provides in most cases excellent visualization of the tumor and its relationship with other parts of the heart.
Keywords: myxoma; heart atria; dyspnea; aged; diagnosis; cardiac surgical procedures; treatment outcome